Hibernating bat species of Belarus: results of the work of the Minsk bat contact centre - Shpak, A. (Theriologia Ukrainica, 2018)
Bat contact centres are organizations that exist in a number of countries and are engaged in popularization work, informational support for people facing bats, as well as rehabilitation and temporary maintenance of animals threatened with death during hibernation period. The data obtained during the activity of Minsk bat-contact centre during winter periods of 2007–2016 are presented in the article. In total, 108 hibernating specimens and 5 colonies of 6 species (V. murinus, N. noctula, E. nilssonii, E. serotinus, P. auritus, and P. kuhlii) were registered for 18 localities of Belarus. The dominant among the registered hibernating bats is V. murinus. At the same time, the expansion of the wintering range is shown for V. murinus, N. noctula, and P. kuhlii. The dynamics of the species registrations during the period of the activity of the Centre, as well as during the period of hibernation, are presented. The results of the Centre’s work show the high efficiency of such organizations for the monitoring of fauna and accumulation of scientific information.